The influence of the RQA model on the digital literacy ability of high school students - Silvia Rahmadini; Anik Ghufron; Ahmad Yusuf; Nurul Inayah Khairaty (Himpunan Pengembang Kurikulum Indonesia, 2025)
The digital literacy skills of high school students are still relatively low, especially in critically searching for, evaluating, and managing digital information. This study aims to analyze the effect of the Reading, Questioning, and Answering (RQA) learning model on students' digital literacy skills in Informatics. This study used a quantitative approach with a nonequivalent control group quasi-experimental design involving two classes: an experimental class and a control class, with a sample of 70 grade XI students at SMA Negeri 2 Padang in the 2024/2025 academic year. The research instrument was a digital literacy test covering aspects of online information searching, hypertext navigation, content evaluation, and knowledge compilation. Data analysis was performed using an independent-samples t-test and an N-Gain calculation. The results showed a significant difference in learning outcomes between the experimental and control classes. Students who used the RQA model for learning showed greater improvement across all aspects of digital literacy than those in conventional learning. The RQA model is considered effective because it encourages active engagement, critical thinking, and independent learning among students. Abstrak Kemampuan literasi digital murid SMA masih tergolong rendah, terutama dalam mencari, mengevaluasi, dan mengelola informasi digital secara kritis. Penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran Reading, Questioning, and Answering (RQA) terhadap kemampuan literasi digital murid pada mata pelajaran Informatika. Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi eksperimen nonequivalent control group design yang melibatkan dua kelas, yaitu kelas eksperimen dan kelas kontrol dengan jumlah sampel 70 murid kelas XI SMA Negeri 2 Padang tahun ajaran 2024/2025. Instrumen penelitian berupa tes literasi digital yang mencakup aspek pencarian informasi melalui internet, navigasi hypertext, evaluasi konten, dan penyusunan pengetahuan. Analisis data dilakukan menggunakan uji independent sample t-test dan perhitungan N-Gain. Hasil penelitian menunjukkan adanya perbedaan signifikan antara hasil belajar murid pada kelas eksperimen dan kelas kontrol. Murid yang mengikuti pembelajaran dengan model RQA menunjukkan peningkatan lebih tinggi pada seluruh aspek literasi digital dibandingkan dengan pembelajaran konvensional. Model RQA dinilai efektif karena mampu mendorong keterlibatan aktif, kemampuan berpikir kritis, dan kemandirian belajar murid. Kata Kunci: literasi digital; model pembelajaran; Reading, Questioning, and Answering; RQA